Knowledge, experience and attitudes towards skin‐to‐skin contact following Caesarean sections among health professionals in Vietnam. (28th August 2018) - Tran, Hoang Thi; Nippita, Tanya; Nguyen, Phuong Thi Kim; Nguyen, Phuong Thi Thu; Huynh, Thuy Thi Diem; Hua, Oanh Thi Le; Roberts, Christine L.
Abstract: Aim: This study explored knowledge, experience and attitudes of health professionals towards early essential newborn care and skin‐to‐skin contact following Caesarean sections in a tertiary hospital in Central Vietnam. Method: We conducted a cross‐sectional descriptive study using an anonymous questionnaire in March 2016. Health professionals from obstetrics, anaesthesiology and neonatology departments were surveyed. Results: All of the 204 surveys were returned, accounting for 82% of total staff involved in the care for women and newborns with Caesarean sections. Correct knowledge of early essential newborn care was lowest among anaesthesiology staff. Health professionals reported that ≥90% of Caesarean section births they attended in the preceding week had skin‐to‐skin contact. Approximately 16% obstetricians, 71% midwives, 49% anaesthesiology and 76% neonatology staff considered the current frequency of skin‐to‐skin contact to be about right. The remainder considered the current rate too high. All professional groups identified the main difficulties of conducting skin‐to‐skin contact as the temperature in the operating theatre and the need for additional staff. Other concerns included increasing the risk of the baby of falling off, prolonging the operation and difficulty to monitor mothers. Conclusion: The study identifies issues where improvements can be made in the implementation of skin‐to‐skin contact following Caesarean sections.